ANALISIS FAKTOR- FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMILIHAN TEMPAT PERSALINAN PADA MASA PANDEMI COVID-19 DI PUSKESMAS DELI TUA - Yunita Syahputri Damanik; Nurul Aini Siagian (BEST Journal (Biology Education, Sains and Technology), 2021)
The coverage of deliveries by health workers in Indonesia in 2014, the coverage of delivery assistance by health workers with midwifery competence from 2011 to 2014 tended to increase, namely in 2011 reaching 86.38%, and in 2014 the coverage of delivery assistance by health workers in Indonesia. Indonesia has reached 96.88%. Where this figure has met the target of the 2015 ministry of restra, which is 90%. However, increasing the coverage of birth attendants by health workers in Indonesia has not been matched by an increase in deliveries in health care facilities. Aim; from this study analyzed the factors related to the choice of place of delivery for pregnant women in the second and third trimesters during the Covid-19 pandemic at the N. Purba Maternity Clinic, Medan Sunggal District, Medan City in 2021. Methods; This research is an analytic survey with a cross sectional design using secondary and primary data. This research was conducted at the Deli Tua Health Center. The population in this study were 96 pregnant women. The sample in this study were all pregnant women as many as 96 pregnant women using the slovin formula. Data analysis was performed univariately, bivariately using chi-square. The results of this study are that there is no significant effect between parity and the decision to choose a delivery place with a p-value of 0.19. with the decision to choose a place of delivery with a p-value of 0.02, there is a significant effect between knowledge and the decision to choose a place of delivery with a p-value of 0.003. there is a significant effect between the cost of delivery and the decision to choose a place of delivery with a p-value of 0.01. there is a significant effect between access to health facilities and the decision to choose a place of delivery with a p-value of 0.002. there is a significant effect between husband's support and the decision to choose a place of delivery with a p-value of 0.002, there is a significant effect between health care support and the decision to choose a place of delivery with a p-value of 0.000.